Making Virtual Reality (VR)/Augmented Reality (AR) Possible to Strengthen Disaster Risk Reduction among Communities at Risk of Tsunami - Surtiari, Gusti Ayu Ketut; Dalimunthe, Syarifah Aini; Reksa, Abdul Fikri Angga; Pelupessy, Dicky; Prasojo, Ari Purwanto Sarwo; Jibiki, Yasuhito; Arikawa, Taro (International Journal of Disaster Management, 2023)
This paper aims to seek a deeper understanding of the intention to use Virtual Reality (VR)/ Augmented Reality (AR) to strengthen disaster risk reduction using the technology acceptance model (TAM) among people at risk of a tsunami. Kuta, Bali, Indonesia, was selected as a case study due to its high tsunami risk and dense tourism activities. Data is collected by interviewing 148 households living along the coast who were selected purposively based on the hazard map of the tsunami and the location of tsunami drills in the past, including the proportion of migrants and non-migrants. Studies show that technology is needed to better prepare for future tsunami risks. Despite having experience in tsunami drills, understanding evacuation routes still needs to improve. People perceived VR/AR could provide integrated knowledge and information about tsunamis, including evacuation routes and shelters. Moreover, the VR/AR technology is also perceived to complement existing knowledge and information about coastal protection generated from ecosystem services. The result shows that the intention to use VR/AR is described by the perceived usefulness and perceived ease of use. Significant differences appear among different age groups and are not merely based on migrant's status. This study has an essential impact on policymakers, particularly in proposing the implementation of VR/AR to plan disaster risk reduction effectively.